MODULAR HOUSING FOR YOUNG ADULTS AFFORDABILITY, QUALITY & SITE INTEGRATION - Gedin, Saskia (My University, 2023)
This thesis aims to investigate how residences can be designed as modular structures in cross-laminated timber to create affordable and qualitative housing for young adults that can be easily integrated into different sites to target the housing shortage among young adults in Sweden. The method consists of a combination of theoretical research and research by design to explore the aspects of modularity, affordable housing, residential qualities, and site integration. The research also investigates the potential of using cross-laminated timber as a construction material, given its sustainable profile and production process, suitable for modular design. Theoretical research is conducted by examining methods for affordable housing, an analysis tool for evaluating residential qualities, and approaches to site integration that respect cultural values. The findings are then used to form design strategies that set the basis for a design proposal of a modular apartment series. A design application is thereafter carried out to test the potential of the modular apartment series, where the design proposal is applied to a specific site and context. The chosen site has a high cultural value, making it an interesting subject for evaluating site integration. The chosen context of the design application is student housing, providing a more precise context suitable for the chosen site. The design application evaluates the applicability of the design proposal and its relevance to the research questions and the aim of the thesis. Overall, the thesis presents an in-depth investigation into the potential of modular housing in cross-laminated timber to provide affordable and high-quality residences for young adults in Sweden. The importance of considering site integration and cultural values in the design process is highlighted, along with the practical considerations of using cross-laminated timber as a construction material. The most prominent strategy is found to be to internally optimise similarities in the design to urge affordability and quality while externally allowing for a high degree of customisation to facilitate site integration. The findings can potentially be useful for architects, urban planners, and policy-makers involved in addressing the housing shortage among young adults in Sweden.
Keywords: modular housing, residential qualities, cross-laminated timber